If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8y + 4) + -1(-7y + -7) = -3 Reorder the terms: -1(4 + 8y) + -1(-7y + -7) = -3 (4 * -1 + 8y * -1) + -1(-7y + -7) = -3 (-4 + -8y) + -1(-7y + -7) = -3 Reorder the terms: -4 + -8y + -1(-7 + -7y) = -3 -4 + -8y + (-7 * -1 + -7y * -1) = -3 -4 + -8y + (7 + 7y) = -3 Reorder the terms: -4 + 7 + -8y + 7y = -3 Combine like terms: -4 + 7 = 3 3 + -8y + 7y = -3 Combine like terms: -8y + 7y = -1y 3 + -1y = -3 Solving 3 + -1y = -3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1y = -3 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = -3 + -3 -1y = -3 + -3 Combine like terms: -3 + -3 = -6 -1y = -6 Divide each side by '-1'. y = 6 Simplifying y = 6
| 3y+2x+(y+10)=180 | | 10x+4y=13.5 | | -7(t-3)-(t+4)=3 | | y=-2 | | -6-2b=-4b+3b | | 5x+20=7x-26 | | x=-2 | | 4(4x-6)=2(8x+7) | | x-20=49 | | 12p=20 | | 6(3x-4)-(1-3x)=-67 | | 3a(3a-x)=2b(x+2b) | | 9+17s-4=9s+65-2s | | M+30.0+40=180 | | -7.5x=30.0 | | 4x^2+8x-11=0 | | 3z-7=8 | | 2+3a=11 | | 4x-7(0.03)=79.59 | | 45-4x=5x+21 | | 13-9x=41 | | 12-8x=111-29x | | 90+x+180-90+x=180 | | -5+7a=30 | | -5+7=30 | | 4x^2+4kx+9=0 | | -16-8x=9x+18 | | x-8.4=-5.6 | | 7u-6=29 | | 180-(90+x)+90+x=180 | | s+25=21 | | 7z-6=29 |